2005
DOI: 10.1080/00173130510031636
|View full text |Cite
|
Sign up to set email alerts
|

Airborne birch and oak pollen grains and birch pollen allergens at a common sampling station in Stockholm

Abstract: O. 2005. Airborne birch and oak pollen grains and birch pollen allergens at a common sampling station in Stockholm. -Grana 44: 104-107. ISSN 0017-3134.In the present study, the airborne concentrations of birch and oak pollen grains and birch pollen allergens have been recorded in samples from a common sampling station in Stockholm. The sampling period was between April 22 nd and May 31 st 2003. The objectives were to evaluate if analysis of allergen particles in parallel with pollen grains would be relevant to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 19 publications
1
5
0
Order By: Relevance
“…Ash ( Fraxinus species) pollen was concomitantly sampled with birch pollen but did not cross‐react in our assay (Dr. B. Weber, personal communication). Quercus pollen, reported to contain a cross‐reacting protein with Bet v 1 (22), flew in Munich after the birch pollen season.…”
Section: Resultsmentioning
confidence: 99%
“…Ash ( Fraxinus species) pollen was concomitantly sampled with birch pollen but did not cross‐react in our assay (Dr. B. Weber, personal communication). Quercus pollen, reported to contain a cross‐reacting protein with Bet v 1 (22), flew in Munich after the birch pollen season.…”
Section: Resultsmentioning
confidence: 99%
“…The high peak of birch pollen on 27.4.2010, for example, was a result of longdistance transport between 10 a.m. and 6 p.m. In this case, the pollen count may be misleading, since the pollen grains may have already released their allergenic material into the air and the emptied shells do not provoke allergy symptoms (Rantio-Lehtimäki et al 1994;Holmquist et al 2005). Subjects may also be exposed to small-sized particles possessing allergenic material that cannot be seen in the determination of pollen concentration when using a microscope (Grote et al 2003;Taylor et al 2004;Wang et al 2011).…”
Section: Discussionmentioning
confidence: 97%
“…A number of studies have found that the concentration of pollen in a car’s passenger compartment correlates with the outdoor concentration of pollen. Although the concentration of pollen inside was half that of the outside concentration, it was high enough to lead to symptoms in allergic patients [49, 50]. Opening the windows increased the level of pollen inside the passenger compartment, particularly for the front seats [51].…”
Section: Evaluation Of the Scientific Relevance Of The Guidelinesmentioning
confidence: 99%